2018
DOI: 10.1186/s12903-018-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Probing depth is an independent risk factor for HbA1c levels in diabetic patients under physical training: a cross-sectional pilot-study

Abstract: BackgroundThis cross-sectional study investigates the potential association between active periodontal disease and high HbA1c levels in type-2-diabetes mellitus subjects under physical training.MethodsWomen and men with a diagnosis of non-insulin-dependent diabetes mellitus and ongoing physical and an ongoing exercise program were included. Periodontal conditions were assessed according to the CDC-AAP case definitions. Venous blood samples were collected for the quantitative analysis of HbA1c. Associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
8
0
3
Order By: Relevance
“…These results are consistent with the results of recent studies that have shown that physical activity is associated with a reduced prevalence of periodontitis and improved periodontal health of the population [ 26 28 ]. A study by Su-Jin Han et al [ 27 ] showed a significant association between regular walking and a lower prevalence of periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the results of recent studies that have shown that physical activity is associated with a reduced prevalence of periodontitis and improved periodontal health of the population [ 26 28 ]. A study by Su-Jin Han et al [ 27 ] showed a significant association between regular walking and a lower prevalence of periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of periodontal disease in DM patients is significantly higher than that in non-DM patients [4] . T2DM has a bidirectional relationship with OHQOL [5] , that is, T2DM can lead to an increased incidence of oral diseases, and poor oral health status leads to poor blood glucose control.…”
Section: The Relationship Between Diabetes Mellitus and Oral Health Quality Of Lifementioning
confidence: 85%
“…(1) The effects of T2DM on OHQOL: The salivary gland was damaged; Oral infection; Plasma adiponectin levels changes, whereby DM leads to periodontal vascular damage and weakened Volume 5; Issue 4 mucosal repair, leading to more oral diseases [4] . (2) Effects of OHQOL on T2DM: Low degree inflammation where, periodontitis leads to increased activity of inflammatory factors in the oral cavity, leading to decreased sensitivity to insulin, and aggravating insulin resistance [4] . For tooth loss, the existence of periodontitis leads to fragile tooth matrix, then masticatory dysfunction, followed by nutritional disorders, resulting in poor blood sugar control.…”
Section: The Relationship Between Diabetes Mellitus and Oral Health Quality Of Lifementioning
confidence: 99%
“…Insulin resistance has also been linked to increased susceptibility to infections and altered oral microflora composition [ 58 ]. There is a considerable body of evidence suggesting the existence of a two-way relationship between diabetes and periodontal disease, with diabetes increasing the risk for periodontitis, and periodontal inflammation negatively affecting glycaemic control [ 59 61 ]. Our subjects did not present abnormal glucose levels, but many had elevated insulin resistance index.…”
Section: Discussionmentioning
confidence: 99%